Postoperative hypothermia and patient outcomes after major elective non‐cardiac surgery. (17th April 2013) - Karalapillai, D.; Story, D.; Hart, G. K.; Bailey, M.; Pilcher, D.; Schneider, A.; Kaufman, M.; Cooper, D. J.; Bellomo, R.
Abstract Using a multicentre adult patient database from Australia and New Zealand, we obtained the lowest and highest temperature in the first 24 h after admission to the intensive care unit after elective non‐cardiac surgery. Hypothermia was defined as core temperature < 36 °C; transient hypothermia as a temperature < 36 °C that was corrected within 24 h, and persistent hypothermia as hypothermia not corrected within 24 h. We studied 50 689 patients. Hypothermia occurred in 23 165 (46%) patients, was transient in 22 810 (45%), and was persistent in 608 (1.2%) patients. On multivariate analysis, neither transient (OR = 1.07, 95% CI 0.96–1.20) nor persistent (OR = 1.50. 95% CI 0.96–2.33) hypothermia was independently associated with increased hospital mortality.